NORMATIVE ANALYSIS OF LAND CONTROL FOR THE DEVELOPMENT OF THE ARCHIPELAGO'S CAPITAL - Pinkan Nazhwa Izza Tsabira; Fatimah Asyari; Farahwati; Kamaludin (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
Transfer The National Capital (IKN) from Jakarta to East Kalimantan is milestone big one that carries implications wide to order space, politics agrarian, as well as mastery land in scale massive. Study This analyze in a way normative policy IKN land based on Constitution Number 3 of 2022 in conjunction with Law No. 21 of 2023, Regulation President, and regulation implementer other. Focus study directed on authority IKN Authority (OIKN) in management land, scheme giving right term long (HGU 190 years, HGB up to 160 years), and problem normative consequences​ related certainty, justice, and protection right public local. Findings study show that even though regime law IKN land is designed as lex specialist for support acceleration development, practice procurement land Still leaving overlapping problems overlap claim between country, society customs (ulayat), and used ownership kingdom (sultan grond), accompanied limited protection law to public affected. With use Theory Rawls's justice, function social land, and draft right customary law, research This emphasize that policy IKN land must ensure distribution benefit Andjustice substantive, in particular for group prone to. Recommendation main covering acceleration harmonization regulations national-regional-customary, review repeat scheme right land term length, reinforcement protection right customary law, as well as implementation mechanism participatory and transparent in every Stages mastery land. With However, IKN development is not only oriented on investment and infrastructure, however Also in harmony with Principle justice agrarian and mandate constitution.